Pengembangan Media Video Animasi Motion Graphic Iklan Elektronik Bermuatan Produk Lokal Bengkulu Untuk Meningkatkan Hasil Belajar Pada Pembelajaran Bahasa Indonesia Kelas V di Sekolah Dasar - Uswatun Khasanah, Ana; Muktadir, Abdul; Widi Winarni, Endang (UNIB Press, 2025)
This research and development aims to find out how development, logical feasibility, empirical feasibility, teacher and student responses and the effectiveness of motion graphic animation video media developed at SDN 16 Bengkulu City. The method used is the Research and Development method using the ADDIE model. The research subjects were 30 grade V students and the research object was a motion graphic animated video media product with Bengkulu local products.The research instruments used were interviews, questionnaires, knowledge learning outcomes tests in the form of Multiple Choices and Essays which were given through pretest and posttest. The results of the research show that the developed media meets the eligibility and requirements to be used as learning media. This can be seen from material validation of 0.95, language validation of 0.88 and design validation of 0.92. For students' responses showed a positive response to the media that was developed. As well as being effective enough to improve students' Indonesian learning outcomes. It can be seen from the learning outcomes of the knowledge aspect, the significance value at (2-tailed) is 0.000 and the N-Gain Score is 73%. From these data it appears that there are differences in the learning outcomes achieved by students in the experimental and control classes. Thus it can be concluded that motion graphic-based animated video media is quite effective in improving Indonesian language learning outcomes in electronic advertising materials in elementary schools.